2018
DOI: 10.3390/ijms19061603
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Malignant Pleural Mesothelioma

Abstract: Despite advances in malignant pleural mesothelioma therapy, life expectancy of affected patients remains short. The limited efficiency of treatment options is mainly caused by inter- and intra-tumor heterogeneity of mesotheliomas. This diversity can be observed at the morphological and molecular levels. Molecular analyses reveal a high heterogeneity (i) between patients; (ii) within different areas of a given tumor in terms of different clonal compositions; and (iii) during treatment over time. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 62 publications
1
38
0
Order By: Relevance
“…Histological subtypes within these three types have been defined (34). The histological classification only partially captures the tumor heterogeneity observed at both the molecular and clinical levels (35). Large-scale omics and NGS studies have demonstrated MPM heterogeneity at the molecular level that goes beyond the histological classification (14,18,36).…”
Section: Mesothelioma Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…Histological subtypes within these three types have been defined (34). The histological classification only partially captures the tumor heterogeneity observed at both the molecular and clinical levels (35). Large-scale omics and NGS studies have demonstrated MPM heterogeneity at the molecular level that goes beyond the histological classification (14,18,36).…”
Section: Mesothelioma Heterogeneitymentioning
confidence: 99%
“…To better define the polyclonal tumor origin and understand the tumor evolution of mesothelioma, further studies are required in a larger number of tumor samples. Several studies also highlighted the presence of cancer stem cells in MPM (35). In MPM, heterogeneity is not limited to tumor cells; the tumor microenvironment is also distinct from one patient to another in terms of type and number of stromal and immune cells that infiltrate the tumors (43).…”
Section: Mesothelioma Heterogeneitymentioning
confidence: 99%
“…MPM displays high heterogeneity, characterized by inter-and intratumor variability at cellular and molecular levels (4,5,126,127). Heterogeneity represents a key mechanism underlying the poor response of MPM patients to current therapeutic interventions and is a challenge in systematic studies aimed at identifying effective treatment and curtailing drug resistance.…”
Section: Further Considerations In Systematic Approachesmentioning
confidence: 99%
“…As well as intertumor heterogeneity, MPM tumors also exhibit intratumor heterogeneity. This tumour complexity limits the ability to delegate suitable treatment options due to the existence of several tumor clones and subclones within a single patient [ 11 ]. Intertumor heterogeneity is inclusive of the variable molecular phenotype of MPM.…”
Section: Introductionmentioning
confidence: 99%